The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1016/s2666-5247(21)00358-x
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and immunogenicity of two recombinant DNA COVID-19 vaccines containing the coding regions of the spike or spike and nucleocapsid proteins: an interim analysis of two open-label, non-randomised, phase 1 trials in healthy adults

Abstract: Background We assessed the safety and immunogenicity of two recombinant DNA vaccines for COVID-19: GX-19 containing plasmid DNA encoding the SARS-CoV-2 spike protein, and GX-19N containing plasmid DNA encoding the SARS-CoV-2 receptor-binding domain (RBD) foldon, nucleocapsid protein, and plasmid DNA encoding the spike protein. Methods Two open-label non-randomised phase 1 trials, one of GX-19 and the other of GX-19N were done at two hospitals in South Korea. We enrolled… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 24 publications
1
38
0
1
Order By: Relevance
“… 8 To our knowledge, in addition to COH04S1 only two other SARS-CoV-2 vaccines co-expressing spike and nucleocapsid are being tested in the clinic. 9 , 10 COH04S1 showed potent immunogenicity in mice, 7 and studies in hamsters and non-human primates showed protection by COH04S1 against upper and lower respiratory tract infection following SARS-CoV-2 challenge. 11 We aimed to assess the safety and immunogenicity of COH04S1 in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“… 8 To our knowledge, in addition to COH04S1 only two other SARS-CoV-2 vaccines co-expressing spike and nucleocapsid are being tested in the clinic. 9 , 10 COH04S1 showed potent immunogenicity in mice, 7 and studies in hamsters and non-human primates showed protection by COH04S1 against upper and lower respiratory tract infection following SARS-CoV-2 challenge. 11 We aimed to assess the safety and immunogenicity of COH04S1 in healthy adults.…”
Section: Introductionmentioning
confidence: 99%
“…An outcome of sterilizing immunity is reducing incidence of viral transmission between the infected and the uninfected, which we successfully demonstrated. The ability to elicit mucosal immune responses and directly dampen transmission even with the Omicron VOC differentiates NanoSTING-NS from IM multi-antigen vaccines 49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…If at least two dilutions of each sample were not included within the standard curve due to low OD value, then the sample was considered as 0.5 BAU/mL. To measure the SARS-CoV-2-specific neutralizing antibody activity induced by the vaccine, a FRNT was performed using Wuhan strain of SARS-CoV-2 using qualified methods as described previously [ 14 ].…”
Section: Methodsmentioning
confidence: 99%